Genetic deficiency or pharmacological inhibition of miR-33 protects from kidney fibrosis - Price, Nathan L. (JCI Insight, 2019)
Previous work has reported the important links between cellular bioenergetics and the development of chronic kidney disease, highlighting the potential for targeting metabolic functions to regulate disease progression. More recently, it has been shown that alterations in fatty acid oxidation (FAO) can have an important impact on the progression of kidney disease. In this work, we demonstrate that loss of miR-33, an important regulator of lipid metabolism, can partially prevent the repression of FAO in fibrotic kidneys and reduce lipid accumulation. These changes were associated with a dramatic reduction in the extent of fibrosis induced in 2 mouse models of kidney disease. These effects were not related to changes in circulating leukocytes because bone marrow transplants from miR-33–deficient animals did not have a similar impact on disease progression. Most important, targeted delivery of miR-33 peptide nucleic acid inhibitors to the kidney and other acidic microenvironments was accomplished using pH low insertion peptides as a carrier. This was effective at both increasing the expression of factors involved in FAO and reducing the development of fibrosis. Together, these findings suggest that miR-33 may be an attractive therapeutic target for the treatment of chronic kidney disease.